Effect of brown algae on germination, growth and biochemical composition of tomato leaves (Solanum lycopersicum) - Said Baroud; Saida Tahrouch; Khadija El Mehrach; Issam Sadki; Fadma Fahmi; Abdelhakim Hatimi (Journal of the Saudi Society of Agricultural Sciences)
This current work, examines the effects of three brown algae (Cystoseira gibraltarica, Fucus spiralis and Bifurcaria bifurcata) as biostimulant on the germination and the growth of tomato (Solanum lycopersicum) in vitro, in addition to the greenhouse. The different treatments (Amendment/aqueous extracts) had been tested with varied concentrations. The obtained results proved that the seeds which received the extracts of C. gibraltarica and B. bifurcata at feeble concentration (0.5%) were lightly germinated with high length of hypocotyls and radicle. The F. spiralis alga extract ameliorated the rate of germination, the length of the hypocotyls and of the radicle for the three concentrations. Moreover, all concentrations improved seedling biomass. The growth pourcentage in the greenhouse (the aerial part length, the root’s length, total length and dry weights) was higher in the plants that received a weak concentrations of extracts of the algae B. bifurcata, C. gibraltarica and F. spiralis. Furthermore, the biochemical composition of plants treated with B. bifurcata and F. spiralis extract at low concentration were improved. This study came up with interesting information about F. spiralis and B. bifurcata species could be regarded as an excellent biostimulant to improve the tomato growth.